STATUS KEWARGANEGARAAN ANAK SEBELUM ADANYA UNDANG-UNDANG KEWARGANEGARAAN NO. 12 TAHUN 2006 TENTANG KEWARGANEGARAAN - Handayani, Pristika; Giyono, Urip (Jurnal Jendela Hukum, 2023)
The purpose of this paper is to analyze normatively regarding children resulting from marriages of different citizens, which in this case is regulated in law number 12 of 2006 concerning citizenship. Children from mixed marriages have the right to determine or choose citizenship. In the case of a child's citizenship, it can be obtained after the child is 18 (eighteen) years old. Children can determine their own citizens because they are considered adults in accordance with the provisions stipulated in the Civil Code. With the regulations governing citizenship, it is hoped that later there will be no unrest for children, and also children's rights will be maintained, especially in terms of administration in Indonesia.